Corticosteroid phobia among parents of asthmatic children - (:unkn) unknown (TURKISH J PEDIATRICS, 2018)
Asthma is one of the most prevalent chronic diseases among children. Its prevalence and morbidity have been rising in recent decades. Pediatric asthma causes a significant burden on families; allergen-avoidance measures, uncontrolled disease, and disease severity which are the major cost predictors of childhood asthma in Turkey. Inhaled corticosteroids (ICS) are considered as cornerstone medications in asthma management which reduce asthma morbidity and mortality. Our aim was to address corticosteroid phobia in caregivers of asthmatic children and its impact on asthma management. Five hundred caregivers of asthmatic children were interviewed using structured questionnaire in this study. Over fifty percent of the caregivers (56.8%), most of whom (82.6%) are already aware of using corticosteroids in their anti-asthma drug regimen, mentioned that they are afraid of using them. Almost one fourth of caregivers (24.8%) made either some changes in their treatment regimen or stopped using the drugs due to corticophobia. Of the caregivers 55.2% had no idea about the side effects of corticosteroids and only 12.6% of them mentioned that they were informed by their physicians about the effects of corticosteroids. Any change in asthma treatment regimen due to corticophobia was found to be related with poor asthma control level (p: 0.004). The impact of parental information about the effects and importance of steroids given by the physicians on better asthma control was found to be highly significant (p < 0.001). That's why physicians and health care providers should spend enough time explaining the importance of adherence to treatment in asthma management, which may help in overcoming the fear of using ICS.
Keywords: asthma; children; corticosteroids; phobia; INHALED CORTICOSTEROIDS; CHILDHOOD ASTHMA; PATIENTS BELIEFS; STEROID PHOBIA; BECLOMETHASONE; ADHERENCE; IMPACT; NONADHERENCE; MEDICATIONS; PREVALENCE